Utilização de controle suplementar de amortecimento em compensadores estáticos síncronos para melhoria de oscilações interárea considerando múltiplos cenários operativos - Galassi, Paulo Henrique (2022)
Electromechanical oscillations are a common phenomenon and of vital concern for the safe operation of electrical systems. With the growth of the interconnection of large systems, which may cross national borders, the emergence of these oscillations with low damping coefficients has intensified, especially interarea oscillations. For this, the implementation of PSS controllers in synchronous generators has been adopted as the main solution to improve the damping coefficient, becoming an essential equipment for the safety and continuity of the electrical system operation. In the event of failure or unavailability of this equipment, it is necessary that another damping source is capable of contributing to guarantee the minimum stability margin of the oscillation mode until the main controller returns to operation. In this context, this work aims to study the adjustment and performance of a STATCOM POD controller for the improvement of the damping coefficient of an interarea oscillation mode, considering its influence in multiple operating scenarios when the main PSS controllers associated in this way. The POD controller is adjusted through a three-step sequential methodology, which aims at mitigating possible adverse voltage transient effects, meeting the specified damping coefficient requirement, by the damped Nyquist method, and minimizing the control effort at low magnitude sustained deviations in the controller input signal. As a study case and motivation for the development of this work, the application of this methodology and the analysis was developed by simulation in ANAREDE, ANATEM and PacDyn for a predicted real implementation of a STATCOM POD controller connected to the Paraguayan-Argentinean-Uruguayan interconnected electrical system. The results showed that the STATCOM equipped with the POD controller proved to be robust as a backup for the improvement of the interarea mode damping coefficient against small disturbances, but it has limited capacity depending on the intensity of the disturbance. Additionally, the POD controller contributes positively when in conjunction with the main PSS controllers to improve the system stability.